MODELING THE MANAGEMENT OF INNOVATION RISKS AT THE INVESTMENT STAGE OF ENTERPRISEACTIVITY - MYKYTYUK, Yuliia; ANDRIYOVSKYI, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Innovative activities of enterprises today play a key role in ensuring their competitiveness and sustainable development. Risk management at the investment stage is especially important, when decisions on the implementation of new products, technologies or projects determine the economic efficiency and long-term stability of the enterprise. In conditions of high uncertainty, traditional risk management methods often prove to be insufficiently effective, which requires the use of a systematic approach and mathematical modeling. Considerable attention should be paid to external factors, in particular, risks associated with military operations and political instability. War creates additional threats to investment activities: exchange rate fluctuations, disruption of logistics chains, reduction of financial resources, reduction of demand and increased uncertainty in the market. This necessitates the development of risk management models that can quickly adapt to changes in the external environment and support effective decision-making even in crisis conditions. Special attention is paid to approaches to modeling innovation risk management at the investment stage of an enterprise’s activities, taking into account external threats, in particular those arising from military conflicts. Such a systematic approach allows not only to identify potential risks, but also to assess their impact on investment projects and develop mechanisms to minimize negative consequences.